Comparison of Antioxidant Properties of Fruit from Some Cultivated Varieties and Hybrids of Rubus idaeus and Rubus occidentalis - Natalia Adamczuk; Mirosława Krauze-Baranowska; Justyna Ośko; Małgorzata Grembecka; Piotr Migas (Antioxidants)
The aim of this study was to compare the antioxidant potential in the fruits of different hybrids of Rubus idaeus and Rubus occidentalis (four hybrids) against the fruit of known cultivars of both species (R. idaeus—three cultivars; R. occidentalis—five cultivars) and, using chemometric analysis, to select factors affecting the level of polyphenols and antioxidant properties. Antioxidant activity was determined using the ABTS, DPPH and FRAP tests. Chemometric analysis enabled the separation of R. idaeus and R. occidentalis cultivars and classified the hybrid R. idaeus/R. occidentalis R1314701 as belonging to the R. occidentalis species. Moreover, two hybrids, Rubus occidentalis/Rubus idaeus R1613411 and R. idaeus/R. occidentalis R1613409, can be classified as a purple raspberry. Crossbreeding species/cultivars of the Rubus genus may result in an increased content of anthocyanins, but on the other hand, it may lead to a reduction in free radical scavenging activity in the ABTS and DPPH. Spearman’s correlations confirm the correlations between the total polyphenol content and antioxidant activity in the DPPH, ABTS and FRAP, as well as the anthocyanin content and antioxidant activity in the ABTS and FRAP tests. Chemometric analysis can be an effective tool in determining the species affiliation of obtained hybrids and cultivars.